2018
DOI: 10.1103/physrevb.98.035102
|View full text |Cite
|
Sign up to set email alerts
|

Persistent low-energy phonon broadening near the charge-order q vector in the bilayer cuprate Bi2Sr2CaCu2O8+

Abstract: We report a persistent low-energy phonon broadening around qB ∼ 0.28 r.l.u. along the Cu-O bond direction in the high-Tc cuprate Bi2Sr2CaCu2O 8+δ (Bi-2212). We show that such broadening exists both inside and outside the conventional charge density wave (CDW) phase, via temperature dependent measurements in both underdoped and heavily overdoped samples. Combining inelastic hard x-ray scattering, diffuse scattering, angle-resolved photoemission spectroscopy, and resonant soft x-ray scattering at the Cu L3-edge,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
24
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 50 publications
4
24
1
Order By: Relevance
“…This line of thinking is consistent with the enhancement of the CDW in monolayer VSe 2 , T CDW = 220 K 28 , since the out-of-plane van der Waals interactions are absent in this case. The critical role of out-of-plane coupling of layers has also been highlighted in the development of the 3D CDW in high-Tc cuprate superconductors [39][40][41] .…”
Section: Discussionmentioning
confidence: 99%
“…This line of thinking is consistent with the enhancement of the CDW in monolayer VSe 2 , T CDW = 220 K 28 , since the out-of-plane van der Waals interactions are absent in this case. The critical role of out-of-plane coupling of layers has also been highlighted in the development of the 3D CDW in high-Tc cuprate superconductors [39][40][41] .…”
Section: Discussionmentioning
confidence: 99%
“…1). Even if a substantial amount of the excess charge goes onto the chain Cu, HPO compounds still differ significantly from the phase diagram as it applies to conventionally "overdoped" materials (23,24), in that T c shows no indication of rolling over up to the highest p values. X-ray measurements (25) and valence-bond sum calculations (26) that concur with the optimum p value for O 2 -doped cuprates do, however, confirm that p does exceed 0.3 for HPO YSCO-Mo and related (Cu-Mo)-12s2 superconductors.…”
mentioning
confidence: 97%
“…Experimentally, however, anomalous isotope effects (5), resonant ultrasound (6), angle-resolved photoemission spectroscopy (7)(8)(9), femtosecond optical pump terahertz (10)/megaelectron-volt transmission electron microscopy probe (11), infrared pump (12), and so on have demonstrated that specific phonons not only couple to the superconductivity but correlate directly with the gap energy and may even transiently induce it well above the superconducting critical temperature, T c . Cuprates also exhibit a plethora of superstructures indicative of strong electron-lattice coupling, stripes that have been proposed to stabilize the superconductivity (13), and charge-density waves (14,15) and the pseudogap (PG) (16) that compete with it. Another possibility is mechanisms that boost T c from a low value expected within a conventional Bardeen-Cooper-Schrieffer (BCS) scheme.…”
mentioning
confidence: 99%